Perencanaan Habitat Burung Kokokan untuk Mendukung Pengembangan Wisata Banjar Petulu Gunung, Desa Petulu, Gianyar-Bali - Putra, Kadek Raditya Permana; Yusiana, Lury Sevita; Yuni, Luh Putu Eswaryanti Kusuma (Jurnal Arsitektur Lansekap, 2023)
Planning of Heron Habitat to Support Tourism Development in Banjar Petulu Gunung Desa Petulu. Banjar Petulu Gunung is one of the natural attractions in Gianyar that involve the population of the heron as the main attraction. Banjar Petulu Gunung needs a landscape plan because of the decreasing population of heron in March – October that affects the community income from tourism. The aim of this study was to make optimal landscape planning that matches with the behavior of heron habits in Banjar Petulu Gunung. The method used for the research was observation with line transect method, interviews, and literature study. The stages of this research were the preparation, data inventory, data analysis and synthesis, and landscape planning. The data analysis was followed by the behavior and the habitats of heron with line transect method. The data analysis result produces the data synthesis for landscape planning. There are four areas that can optimize for the natural development as a habit of heron which is corridors side of the road, ex-captivity, pond, and best view area as the main. The vegetation was arranged with the dominant tree as behavior support of heron that used for foraging, stay, moving, reproduction, agonistic, and preening. Planning on the site can be arranged for balance the heron habits and tourism income in Banjar Petulu Gunung, Desa Petulu, Kabupaten Gianyar.